2021
DOI: 10.1002/mma.7799
|View full text |Cite
|
Sign up to set email alerts
|

Effects of toxicity and zooplankton selectivity on plankton dynamics under seasonal patterns of viruses with time delay

Abstract: Intricate functional diversities in marine ecosystems often lead to exhibit a variety of dynamical behaviors, including chaos. To bring order into such chaotic situations, the system develops different mechanisms of self‐adaptability. Our present investigation is based on the study of an eco‐epidemiological model for virally infected toxic phytoplankton and zooplankton system. Both healthy and infected phytoplankton are assumed to be exposed to grazer zooplankton with a varying degree of exposure. An extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Every biological process is time-consuming. 9,12,35,36 For example, a parasite's transfer from an infected individual to a susceptible one is not instantaneous. Therefore, the impact of this time delay (or, incidence delay) can't be ignored.…”
Section: 𝛽𝑆𝐼 𝑆+𝐼mentioning
confidence: 99%
See 2 more Smart Citations
“…Every biological process is time-consuming. 9,12,35,36 For example, a parasite's transfer from an infected individual to a susceptible one is not instantaneous. Therefore, the impact of this time delay (or, incidence delay) can't be ignored.…”
Section: 𝛽𝑆𝐼 𝑆+𝐼mentioning
confidence: 99%
“…They have shown that the system executes a strange attractor via limit cycle for a higher value of incidence delay, but a lower infection rate can annihilate the impact of incidence delay. Biswas et al 36 investigated the effect of time delay in phytoplankton (susceptible and infected) and zooplankton ecosystems with seasonally dependent virus replication patterns. They observed that the system's dynamics (stable, periodic, and chaotic) switches several times due to the variation of delay parameter.…”
Section: 𝛽𝑆𝐼 𝑆+𝐼mentioning
confidence: 99%
See 1 more Smart Citation